CSR: A CASE STUDY OF STARBUCKS IN INDIA - Shaikh, Mohammed Sameer (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Starbucks has been successfully growing its stores and presence in India, and described the profitable growth to its investors as something it wanted to build in other international markets and choose India as one of its international markets. Starbucks established its first store in India on 19th October 2012 at Elphinstone building, Horniman Circle in Mumbai measuring 4,500 sq ft. Starbucks also opened its first plant of roasting and packaging to supply its Indian outlets at Kodagu, Karnataka in 2013. Starbucks is operating in India from past 9 years and opened 216 outlets all over India with 50:50 joint venture company owned by Starbucks Corporation and Tata Consumer Products known in India as Tata Starbucks Limited. This research study is designed to understand the corporate social responsibility (CSR) and identify the scope of saving tax by offering social responsibilities, taking the case study of Starbucks in India. The study of this paper has described strategies, legal, ethical, public relations and tax minimization strategies, of companies like Starbucks that portray themselves as responsible “citizens” of the society in which they operate.